Objective measurement of physical activity in overweight and obese pregnant women. (16th November 2010) - McParlin, C; Kinnunen, TI; Tennant, PWG; Poston, L; Bell, R; Robson, SC
Abstract : Introduction: Promoting increased physical activity (PA) during pregnancy could decrease the risk of obesity related pregnancy complications. At least 30 min of moderate or vigorous activity (MVPA) or 8000 steps/day are recommended. There is little information on PA levels in pregnant women. Self-report measurement methods tend to overestimate PA. This study assessed PA in overweight and obese pregnant women objectively using accelerometers and pedometers. Methods: 65 pregnant women, body mass index (BMI) >25 kg/m 2, consented and had their PA measured for at least three valid days, using both measurement tools. Their mean age was 31.3 years (SD=5.6), mean BMI 31.2 kg/m 2 (SD=5.5) and median gestation 13 weeks (IQR=12–20), 60% were overweight, 40% obese and 46% nulliparous. Results: 46% of women recorded ≥30 min/day MVPA via accelerometry while 30% recorded ≥8000 steps via pedometry. The mean step counts by accelerometry and pedometry were 6007 (SD=2039) and 5933 (SD=2777). Despite the small mean difference there was substantial intrapersonal disagreement, (limits of agreement= −3389 to 3357 steps/day). There were no differences in any of the PA variables between overweight and obese women. Multiparous women recorded more time in light PA, (3 h 31 min, SD=47 min), than nulliparous women, (2 h 41 min, SD=45 min, p<0.001), while nulliparous women recorded more sedentary time, (10 h 15 min, SD=1 h 9 min, compared to 9 h 25 min, SD=1 h 44 min, p=0.031). There were no parity differences in the proportion of participants achieving recommended PA guidelines. Conclusion: Only 46% of participants achieved the recommended 30 min of MVPA/day, fewer achieved recommended step counts. Interventions to improve PA levels should target moderate intensity activities such as brisk walking.